Cervical Cancer Screening with HPV Testing: Updates on the Recommendation - Carvalho, Carla Fabrine; Teixeira, Julio Cesar; Bragança, Joana Froes; Derchain, Sophie; Zeferino, Luiz Carlos; Vale, Diama Bhadra (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
The present update is a reassessment of the 2018 ‘Guidelines for HPV-DNA Testing for Cervical Cancer Screening in Brazil’ (Zeferino et al.)9, according to the changes observed in new international guidelines and knowledge updates. The most relevant and recent guidelines were assessed. Questions regarding the clinical practice were formulated, and the answers considered the perspective of the public and private sectors of the Brazilian health system. The review addressed risk-based strategies regarding age to start and stop screening, the use of cytology and colposcopy to support management decisions, treatment, follow-up strategies, and screening in specific groups, including vaccinated women. The update aims to improve the prevention of cervical cancer and to reduce overtreatment and the misuse of HPV testing.
Keywords: uterine cervical neoplasms; human papillomavirus DNA tests; early detection of cancer; accessibility of health services; mass screening